Speeches, geopolitical and zionism in the palestinian - israeli conflict. a systemic analysis (2011)
The Israeli-Palestinian conflict scenario analysis suggests that part of the construction of national discourses mediated by systemic political and economic interests and not only of endogenous elements as proposed by the common reading of Zionism. From there, the originality of national discourses based on religious grounds should be reviewed to understand transverse processes conceal hegemonic interests. However, religious discourses that have intervened along the Israeli-Palestinian conflict, with greater intensity after the 1967 war, have been a catalyst for expressions of religious Zionism, obscuring geopolitical interests for territorial control in Palestine.